A cycloruthenated complex: Detecting Hg2+ by Hg2+‐promoted coordination switch and Cu2+ by coordination. (19th July 2022) - Xu, Ce; Du, Kang; Wu, Yuhao; Tan, Lin; Li, Xianghong
Abstract : A new cycloruthenated complex Ru1 with a ditopic thienyl–NHC ligand has been designed to recognize Hg 2+ by a blue shift in absorption and evident solution color change in aqueous system. However, the time‐dependent absorption spectral changes of Ru1 with Hg 2+ and H + as well as MS and 1 H NMR spectra demonstrated a possible Hg 2+ ‐promoted coordination switch from Ru‐C to Ru‐S. Moreover, it should be noted that different color and absorption spectral changes were also observed in the presence of Cu 2+ . The reversible behavior between Ru1 ‐Cu 2+ and HS − indicated a simple coordination between Ru1 and Cu 2+ . As a result, the different interactions between Ru1 and the two metal ions demonstrated a possible way for Ru1 to detect Hg 2+ and Cu 2+, respectively. Furthermore, Ru1 was also used to determine Hg 2+ and Cu 2+ in some spiked water samples, respectively. Abstract : A cycloruthenated complex can be used as an irreversible probe to detect Hg 2+ by an Hg 2+ ‐promoted coordination switch. However, the simple coordination between Cu 2+ and the complex provided reversibility at least five times to detect Cu 2+ .